Nazism across borders: the social policies of the Third Reich and their global appeal - Kott, Sandrine; Patel, Kiran Klaus (Oxford University Press, 2018)
Nazism across Borders argues that Nazi social policies were part of transnational exchanges and processes. Beyond territorial conquest, the Nazis planned to export and internationalize their version of welfare, and 26381promoted a new kind of internationalism, pitched as a superior alternative to its liberal and Communist contenders.Since the late nineteenth century, the 'German social model' had established itself as a powerful route for escaping from the precarious conditions associated with wage work. The Nazis capitalized on this reputation, continuing some elements, but also added new measures, mainly to pursue their antisemitic, racist, and highly aggressive goals. The contributions in this collection shed new light on the complex ways in which German and Nazi ideas were received and negotiated by non-German actors and groups around the world before the Second World War. Why were they interested in what was going on in Germany? To what extent did Nazi policies emulate programmes elsewhere (for example, in Fascist Italy), and where did they serve as role models? Nazi social policies, we argue, were a benchmark that societies as diverse as Japan, Norway,and the United States considered in making their own choices. Nazism across Borders breaks new ground for the history of the Second World War and 'Hitler's empire' in Europe. How did the Nazis export their ideas when they finally occupied large swaths of the continent and what was the role of non-German actors? What were the links to the better-known stories of exploitation of lands, resources, and peoples?
Foreword: "Nazism across borders" is the result of a conference held at the German Historical Institute London in 2015
Register Seite [425]-436
Keywords: Geschichte 1933-1945; Protektorat Böhmen und Mähren; Konferenzschrift -- 2015 -- London; Aufsatzsammlung; Rezeption; Internationalismus; Sozialpolitik; Nationalsozialismus; Deutschland